Decarbonizing North America’s rail sector, international initiatives and local opportunities - Mohsen Mandegari; Mahmood Ebadian; Jack (John) Saddler (Transportation Research Interdisciplinary Perspectives, 2023)
North American rail is unlikely to be electrified in the near term. Although strategies such as improving fuel efficiency, enhanced logistics, etc., are already being pursued, the primary way to reduce the carbon intensity (CI) of the rail sector will be through the use of low-CI fuels such as bio/renewable diesel. Alternatives such as battery-electric and hydrogen fuel cells are still evolving and, while liquid/compressed natural gas (LNG/CNG) can be used as “transition (lower-CI) fuels”, they are not drop-in, requiring considerable investment in engines and infrastructure. By contrast, bio-based diesels are low-carbon solutions that can be readily deployed to reduce rail associated GHG emissions. However, the high price of bio-based diesels, competition with other modes of transport (e.g., trucking), and the lack of “enabling” policies have limited bio/renewable diesel use by the rail sector. Canada’s current biodiesel production could supply 40% of Canada’s rail sector fuel needs, reducing its GHGs by about 34%.